2023
DOI: 10.3847/2041-8213/acbf41
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Formation of Ethynylbutatrienylidene (HCCCHCCC; X1A′) in the Taurus Molecular Cloud (TMC-1) via the Gas-phase Reaction of Tricarbon (C3) with the Propargyl Radical (C3H3)

Abstract: The recent astronomical detection of ethynylbutatrienylidene (HCCCHCCC)—a high-energy isomer of triacetylene (HCCCCCCH) and hexapentaenylidene (H2CCCCCC)—in TMC-1 puzzled the laboratory astrophysics community since proposed reaction pathways could not synthesize the ethynylbutatrienylidene (HCCCHCCC) under cold molecular cloud conditions. Exploiting a retrosynthesis coupled with electronic structure calculations and astrochemical modeling, we reveal that observed fractional abundance of ethynylbutatrienylidene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…32 Interestingly, it has been observed that C 2 H 3 and C 3 H 3 are noteworthy precursors in the synthesis of the cyclopentadienyl radical, 3 which has the potential to engage in interactions with methyl radicals, leading to the expansion of benzene and ultimately culminating in the synthesis of polycyclic aromatic hydrocarbons (PAHs) inside circumstellar environments. 3,33 The present study has shown that aniline dication fragments are C n H 3 + ( n = 1, 2, and 3) and that they can participate in the ion–molecule process in the synthesis of larger molecules due to their significant range of kinetic energies if aniline is present in the ISM.…”
Section: Resultsmentioning
confidence: 68%
“…32 Interestingly, it has been observed that C 2 H 3 and C 3 H 3 are noteworthy precursors in the synthesis of the cyclopentadienyl radical, 3 which has the potential to engage in interactions with methyl radicals, leading to the expansion of benzene and ultimately culminating in the synthesis of polycyclic aromatic hydrocarbons (PAHs) inside circumstellar environments. 3,33 The present study has shown that aniline dication fragments are C n H 3 + ( n = 1, 2, and 3) and that they can participate in the ion–molecule process in the synthesis of larger molecules due to their significant range of kinetic energies if aniline is present in the ISM.…”
Section: Resultsmentioning
confidence: 68%
“…The formation mechanisms of polycyclic aromatic hydrocarbons (PAHs) along with their unsaturated precursors have received considerable attention by the astrochemistry and combustion science communities. Here, PAHs are classified as reaction intermediates and fundamental molecular building blocks in molecular mass growth processes leading ultimately to soot particles (combustion flames) and carbonaceous nanoparticles (circumstellar and interstellar grains). , Particular interest has been devoted to the propargyl radical (H 2 CCCH, X 2 B 1 ), which represents a prototype of a resonantly stabilized free radical (RSFR) and the most thermodynamically stable C 3 H 3 isomer . Recently detected in the cold Taurus Molecular Cloud (TMC-1), bimolecular propargyl–propargyl radical reactions lead to the formation of the aromatic phenyl radical (C 6 H 5 ), while a stabilization of the reaction intermediate(s) accesses benzene (C 6 H 6 ) along with its 1,5-hexadiyne, fulvene, and 2-ethynyl-1,3-butadiene isomers. Consequently, the propargyl radical plays a major role in astrochemical and combustion models as a potential precursor for bottom-up synthetic pathways to PAHs and carbonaceous nanoparticles (soot, interstellar grains). However, reactions of the propargyl radical with closed-shell hydrocarbons, e.g., acetylene (C 2 H 2 ) and benzene (C 6 H 6 ), involve entrance barriers to addition typically in the range of 50–60 kJ mol –1 . These entrance barriers limit propargyl radical reactions with closed-shell hydrocarbons to high-temperature environments like circumstellar envelopes of carbon stars and planetary nebulae as their descendants.…”
Section: Introductionmentioning
confidence: 99%
“…However, reactions of the propargyl radical with closed-shell hydrocarbons, e.g., acetylene (C 2 H 2 ) and benzene (C 6 H 6 ), involve entrance barriers to addition typically in the range of 50–60 kJ mol –1 . These entrance barriers limit propargyl radical reactions with closed-shell hydrocarbons to high-temperature environments like circumstellar envelopes of carbon stars and planetary nebulae as their descendants. So far, the reaction of tricarbon (C 3 )formally a carbenewith the propargyl radical represents the only barrierless and exoergic pathway of the propargyl radical with a technically closed-shell ‘organic’ reactant leading to triacetylene (HCCCCCCH) and its high-energy isomer ethynylbutatrienylidene (HCCCHCC). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation